Implications of Standard Clause Changes in Grab Challenge Program on Consumer Rights - Pandju, Sherly Putri; Cherawaty Thalib, Mutia; T. Mandjo, Julius (Universitas Negeri Gorontalo, 2024)
This study aims to analyze the implications of changes to the standard clauses of the Grab challenge program on consumers. The research method used is normative with a statutory approach.The results of the study show that the implications of the standard clause on the Grab challenge program for consumer protection are that the clause contains several things that are detrimental to consumers, such as limiting Grab's liability, providing disproportionate compensation, and the existence of clauses that burden consumers. This is contrary to the principles of consumer protection. Changes to the standard clauses on the Grab challenge program affect consumer rights and obligations, where consumers have more limited rights, such as the right to choose, the right to information, and the right to security. On the other hand, consumer obligations become more burdensome, such as the obligation to accept unilateral changes and the obligation to resolve disputes through alternative dispute resolution.